Multiphase performance and internal flow pattern of helico-axial pumps. Issue 3 (March 2019) - Xu, Y; Cao, S L; Reclari, M; Wakai, T; Sano, T
Abstract: While the performances of pumps are highly affected by the gas content, the growing demand for transportation of liquid and gas mixtures in many industrial fields (e.g. oil and gas upstream, chemical plants, food processing, etc.) pushes the research and development of multiphase pumps. In the present work, two types of multi-stage helico-axial gas-liquid multiphase pumps (without and with splitter blade) were developed and experimentally tested both in single and multiphase conditions. The efficiency of the pumps is satisfactory and the head of the pump with splitter blades exceeds the design target. Both pumps accept high gas volume fractions (up to 50%), which is outstanding among the rotodynamic pumps. The differences between the two types give guidance for the further design and optimization of helico-axial pump. Additional insight in the internal flow is gained using spectral analysis of the pressure fluctuations in the impeller.